Quality Test of Palm Cooking Oil Used Repeatedly Based on Free Fatty Acid Content, Moisture Content, Peroxide Number - Dewi, Pevy Syntia; Ulfah, Maria (Journal of Science and Technology Research for Pharmacy, 2021)
Background: Cooking oil used repeatedly can increase levels of free fatty acids and the number of peroxides in the blood, so that the risk of heart disease and diabetes. Aim: The purpose of the study was to find out the quality of palm cooking oil used repeatedly in tempeh mendoan against organoleptic, moisture content, free fatty acid content and peroxide number content. Method: Samples of palm cooking oil are used to fry tempe mendoan at 105oC for 10 and 60 minutes as much as 1 frying pan per day for 3 days, then the oil is cooled at room temperature and filter the oil so that it does not mix from the rest of the fried tempeh mendoan. Filtered oils are tested for quality with test parameters including organolepty including shape, color, odor, moisture content, peroxide levels, and free fatty acid levels. The data results were compared with sni 01-3741-2002 cooking oil quality standard and each level was analyzed using nonparametric statistics (Kruskall-Wallis) with a confidence level of 95%. Result: Organoleptic test results obtained the form of cooking oil in light yellow to yellow gold at the 10th minute on the 2nd day after 2 frying pans and orange in the 60 minutes after 3 frying pans for 3 days. Moisture content obtained results 2,086± 2,142 (10th minute) and 0.369± 0.304 (60th minute), free fatty acid content obtained results 0.317± 0.044 (10th minute) and 0.337± 0.076 (60th minute), the rate of peroxide numbers obtained resulted in 0.281± 0.090 (10th minute) and 0.386±0.158 (60th minute). Based on statistics tests there are significant differences (<0.05) to the decrease in water content quality, free fatty acid content and peroxide levels in palm oil cooking oil used repeatedly in tempe mendoan.